Thematic characteristics of the orientation part of the English version of Hikayat Deli text - Nurlela Nurlela; Rudy Sofyan; Rohani Ganie (Studies in English Language and Education, 2021)
As the first part of a narrative text, orientation should be able to attract the readers’ attention; therefore, it must be well organized. From the Systemic Functional Linguistics point of view, a well-organized text can be confirmed through its textual metafunction realized in theme and rheme. In addition to confirming a good organization of the clauses, theme-rheme interactions would make the text interesting. This paper aims at describing the thematic characteristics of the orientation of the English version of Hikayat Deli text (the translated text of Hikayat Deli). This study employed the data derived from the orientation part of the English version of Hikayat Deli text which was analyzed using content analysis. The results of data analysis showed that: (1) unmarked themes dominated the use of theme in the orientation part of the English version of Hikayat Deli text, (2) the story characters (participants) were used most frequently as the clause themes, and (3) conjunctions and conjunctives (textual themes) were the elements of multiple themes most frequently used in the orientation part of the English version of Hikayat Deli text. It is concluded that the choice of theme elements helps in constructing a well-organized orientation and in facilitating the easy understanding to readers of what the rest of the text is about.